The association between methionine synthase A2756G polymorphism and hematological cancer: A meta-analysis. Issue 48 (December 2017) - Wu, Bing; Liu, Kang; Yang, Jun-Ping; Hu, Yan; Zhang, Jun; He, Jun-xiang
Abstract: Background: Numerous studies have focused on the association of methionine synthase (MS) A2756G polymorphism and acute hematological cancer risk. However, the results remain inconsistent. Therefore, a meta-analysis was performed to derive a more precise estimate of the association between them. Methods: This meta-analysis involved 25 articles (26 studies) including 8641 hematological cancer patients and 15, 498 controls. The pooled odds ratios (ORs) and their corresponding 95% confidence intervals (CIs) of the association between MS A2756G polymorphism and the risk of hematological cancer were calculated. Results: Overall, no significant increased risks were found between MS A2756G polymorphism and hematological cancer risk under allelic homozygote (GA vs AA: OR = 0.98, 95% CI = 0.89–1.07, P  = .62), heterozygote (GG vs AA: OR = 0.99, 95% CI = 0.85–1.15, P  = .91), dominant (AG+GG vs AA: OR = 0.99, 95% CI = 0.90–1.08, P  = .93), and recessive (GG vs AG+AA: OR = 1.00, 95% CI = 0.86–1.16, P  = .97) models, respectively. In the stratified analyses by ethnicity and source of controls, there were still no significant associations between them in all genetic models. Conclusions: Therefore, these findings demonstrate that MS A2756G polymorphism may not be a risk factor for hematological cancer. Abstract : Supplemental Digital Content is available in the text